Effects of AMP579 and adenosine on L-type Ca2+ current in isolated rat ventricular myocytes - Wang Xiong; Wu Bo-wei; Wu Dong-mei (Acta Pharmacologica Sinica, 2016)
Aim: To compare the effects of AMP579 and adenosine on L-type Ca2+ current (ICa-L) in rat ventricular myocytes and explore the mechanism by which AMP579 acts on ICa-L. Methods: ICa-L was recorded by patch-clamp technique in whole-cell configuration. Results: Adenosine (10 nmol/L to 50 umol/L) showed no effect on basal ICa-L, but it inhibited the ICa-L induced by isoproterenol 10 nmol/L in a concentration-dependent manner with the IC50 of 13.06 umol/L. Similar to adenosine, AMP579 also showed an inhibitory effect on the ICa-L induced by isoproterenol. AMP579 and adenosine (both in 10 umol/L) suppressed isoproterenol-induced ICa-L by 11.1% and 5.2%, respectively. In addition, AMP579 had a direct inhibitory effect on basal ICa-L in a concentration-dependent manner with IC50 (1.17 mumol/L). PD116948 (30 mumol/L), an adenosine A1 receptor blocker, showed no action on the inhibitory effect of AMP579 on basal ICa-L. However, GF109203X (0.4 mumol/L), a special protein kinase C (PKC) blocker, could abolish the inhibitory effect of AMP579 on basal ICa-L. So the inhibitory effect of AMP579 on basal ICa-L was induced through activating PKC, but not linked to adenosine A1 receptor. Conclusion: AMP579 shows a stronger inhibitory effect than adenosine on the ICa-L induced by isoproterenol. AMP579 also has a strong inhibitory effect on basal ICa-L in rat ventricular myocytes. Activation of PKC is involved in the inhibitory effect of AMP579 on basal ICa-L at downstream-mechanism.